2020
DOI: 10.2139/ssrn.3594598
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infections in People with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Objectives: In previous influenza pandemics, bacterial co-infections have been a major cause of mortality. We aimed to evaluate the burden of co-infections in patients with COVID-19. Methods:We systematically searched Embase, Medline, Cochrane Library, LILACS and CINAHL for eligible studies published from 1 January 2020 to 17 April 2020. We included patients of all ages, in all settings. The main outcome was the proportion of patients with a bacterial, fungal or viral co-infection. . Results:Thirty studies inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 40 publications
(65 reference statements)
2
25
0
6
Order By: Relevance
“…In another report that was published from a UK secondary care setting, 27 among 836 patients (3.2%) had early confirmed bacterial isolates identified (0-5 days post-admission), rising to 51 cases (6.1%) during the admission. In a study conducted in Shiraz, Iran, in 2009, Hassanzadeh et al suggested that ICU-acquired infections were documented in 51.7% of ICU patients, with a mortality rate of 10.9% (5 patients) 22,23 . Our finding was relatively higher among other studies.…”
Section: No Growthmentioning
confidence: 99%
“…In another report that was published from a UK secondary care setting, 27 among 836 patients (3.2%) had early confirmed bacterial isolates identified (0-5 days post-admission), rising to 51 cases (6.1%) during the admission. In a study conducted in Shiraz, Iran, in 2009, Hassanzadeh et al suggested that ICU-acquired infections were documented in 51.7% of ICU patients, with a mortality rate of 10.9% (5 patients) 22,23 . Our finding was relatively higher among other studies.…”
Section: No Growthmentioning
confidence: 99%
“…In another report that was published from a UK secondary care setting, 27 among 836 patients (3.2%) had early confirmed bacterial isolates identified (0-5 days post-admission), rising to 51 cases (6.1%) during the admission. In a study conducted in Shiraz, Iran, in 2009, Hassanzadeh et al suggested that ICU-acquired infections were documented in 51.7% of ICU patients, with a mortality rate of 10.9% (5 patients) 21,22 . Our finding was relatively higher among other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among gram-negative bacteria, the Enterobacteriaceae family being the most commonly found and multidrug-resistant organisms, including Pseudomonas aeruginosa, Acinetobacter baumannii, and extended-spectrum β-lactamase (ESBL)producing or carbapenemase-producing Enterobacteriaceae, are increasingly being reported worldwide 23 . The identification of bacterial infection with gram-negative organisms is more reflected as a complication of ICU care and is not suggested as a specific predilection for co-infections in COVID-19 22 .…”
Section: Discussionmentioning
confidence: 99%
“…We got 75% lung involvement in HRCT chest on Day 20. The increased levels of all these markers also seem to indicate the onset of a cytokine storm in patients 12 .…”
Section: Daymentioning
confidence: 96%
“…In a study by Chen et al 52% of patients had elevated IL-6 levels at admission. Increased IL-6 levels have been associated with increased risk of death 12 . In our case we could not do the IL-6 level.This was our limitation.…”
Section: Daymentioning
confidence: 99%